Islamic Work Ethics and Economic Development in Islamic Countries: Bridging Between Theory and Reality - Ibrahim, Azharsyah (International Conference of Moslem Society, 2018)
The issue work ethic and religion become popular when Max Weber developed a theory on Protestant Work Ethics (PWE) which seems later is able to reinforce the Western economy through its capitalism ideology. In his work, Weber claimed that only the Protestant Christian could accelerate and boost up the economy while none of the eastern religions including Islam would be able to do so. Although many scholars have refused the claim, the backwardness of many Islamic states, ethically and economically, has risen the question about the teaching of Islamic religion on work activities. Therefore, this paper aims to explore the concept of work ethics from an Islamic perspective. In specific, it intends to extract the concept, principle, dimension and values of Islamic Work Ethics (IWE) to be operationalized into daily practices. It revealed that many Quranic verses and Hadiths have directly and indirectly discussed the concept of work ethics in Islam. If properly operationalized, it can bridge the gap between the theory of IWE and the realities of economic development in Islamic states. Adherence to it will influence the economic development in Islamic countries that brings virtuous worldly life (al-falah fi al-dunya), as well as preparing for the success of afterlife (al-falah fi al-akhirah).